Implementasi Metrologi Legal Dalam Peningkatan Pendapatan Daerah: Metrologi Legal - Muldri Pudamo James Pasaribu; Muhammad Yusrizal Adi Syaputra (Jurnal Ilmiah Penegakan Hukum, 2023)
This study aims to determine the authority to collect fees is the authority of local governments to increase regional income. Therefore the mechanism for calculating the tera/recalibration must be carried out as well as possible and have a clear scientific basis. In determining the standardization of measurement and weighing is carried out through a scientific standard known as legal metrology. This research is normative juridical by taking a statutory approach and a conceptual approach. The sources of legal materials that the author uses are primary and secondary legal materials by collecting data through library research and data analysis techniques using content analysis and analytical descriptive. Based on the provisions of Article 1 letter b Law Number 2 of 1981 concerning legal metrology, what is meant by legal metrology is a measurement system that regulates and manages units of measure, measurement methods and measuring instrument standards, which involve technical requirements and regulations based on the Law aims to protect the public interest in terms of the correctness of measurement. Legal basis for determining legal metrology standards: First, Law Number 2 of 1981 concerning Legal Metrology; Second, Government Regulation Number 2 of 1985 concerning Compulsory and Exemption for Calibration and/or Re-calibration and Requirements for Measuring, Measuring, Weighing Instruments and their Equipment; Third, Regulation of the Minister of Trade Number 115 of 2018 concerning Legal Metrology Units; Fourth, Regulation of the Minister of Trade Number 52 of 2019 concerning Legal Metrology Size Standards. The legal metrological calibration/recalibration system can be applied in traditional markets so that market traders are required to pay a levy to obtain calibration/recalibration services related to their scales